Learning based on students’ active participation in transforming theory into practice – as perceived by the students - Høgh, Annie (Improving University Science Teaching and Learning, 2023)
According to the theory of constructivism, learners construct their knowledge with their own activities building on what they already know and understand (Biggs & Tang; 2007, p. 21). Thus, teaching is not a matter of transmitting but of engaging students in active learning. Last autumn I developed a dialogue-based seminar where I gave lectures part of the time and the students participated in discussions, saw film clips and video case stories and analyzed paper-based cases. However, I had the feeling that the students did not really read the mandatory literature, at least not until after a mid-term exam, and that it affected their participation during class. Sometimes it made it difficult to have an active discussion in class. So, in order to further develop the seminar I wanted to encourage student participation by letting them work in groups preparing presentations of theories and models from the mandatory literature for use in analyzing case stories.